The Business of Private Medical Practice : Doctors, Specialization, and Urban Change in Philadelphia, 1900-1940 - Schafer, James A., Jr., 1974- (Book collections on Project MUSE., 2014)
Health care is more expensive in the United States than in other wealthy nations, and access varies significantly across space and social classes. In this case study, James A. Schafer Jr. uses the city of Philadelphia in the early twentieth-century to show that these problems reflect the informal organization of health care in a free market system in which profit and demand, rather than social welfare and public health needs, direct the distribution and cost of crucial resources.